Efektivitas Program Sibakul Jogja dalam Pemberdayaan Mitra UMKM di Yogyakarta - Naami, Mohammad Alvin; Maemunah, Mei (Jurnal Pemerintahan dan Politik, 2024)
This research aims to determine the effectiveness of the Sibakul Jogja Program in empowering MSME partners in Yogyakarta. In this research, the researcher used a qualitative descriptive method where the aim of this method was to be able to describe what happened according to the conditions when the research was carried out. This research uses the Cambell J.P model of program effectiveness theory by looking at the indicators (1) Program Success (2) Overall Goal Achievement (3) Target Success (4) Satisfaction with the Program (5) Level of Input and Output. In this research, researchers have obtained results by carrying out research using the data collection techniques used in this research, namely by conducting interviews and documenting literature studies. The research results show that the Sibakul Jogja Program for Empowering MSME Partners in Yogyakarta has been running effectively. This is proven by the achievement of the criteria for all measurement parameters for each indicator including indicators of Program Success, Overall Goal Achievement, Target Success, Program Satisfaction and Input and Output Levels